Verba Bahasa Melayu Riau Dialek Baturijal Hilir Kecamatan Peranap Kabupaten Indragiri Hulu - Fitria Wulandari; Alber (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
The purpose of this study was to describe and find out data and information about verbs in Riau Malay dialect Batu Rijal Hilir, Peranap District, Indragiri Hulu Regency. The data that has been collected will be described, analyzed, and interpreted systematically so that verbs can be identified in terms of their form in Riau Malay dialect Batu Rijal Hilir, Peranap District, Indragiri Hulu Regency. The method used in this study is an ethnographic method with a qualitative approach. Data collection techniques in this study were interviews, observations, recordings, and notes. The results of this study indicate that (1) Verbs in terms of form consist of: original verbs: [sesa?] 'sesak', [ado] 'ada', [bǝli] 'beli', [balǝ?] 'home', [bayǝ ] 'pay', [tuloƞ] 'help', [broken] 'broke', [gugu] 'fall', [kojo] 'work', [bagƐh] 'beri', [teƞgelam] 'sink'. (2) Derived verbs consist of: (a) Prefix {meN-}: [meniƞok] 'to see', prefix {meN-} The allomorph {meƞ}: [meƞidup] 'to live'. (b) Prefix {ba-}: [babuñi] 'to sound'. (c) Prefix {te-}: [tegayut] 'depends'. (d) Confix {di-}: [dibuƞ?us] 'wrapped'. (e) Confix {di-an}: [dilǝta?kan] 'put', (f) Suffix {-an}: [ambe?an] 'take'. (g) Reduplication of all verbs: [buda?-buda?] 'children'. This shows that the Riau Malay Language Verb in Batu Rijal Hilir Dialect, Peranap District, Indragiri Hulu Regency, in terms of its form, there are two verbs, namely the original verb and the derived verb.